From Opportunity Insight to Opportunity Intention: The Importance of Person–Situation Learning Match - Dimov, Dimo (Entrepreneurship Theory and Practice, 2007)
Within the context of opportunity development as a learning process, this paper explores the intentionality that drives the early stages of this process, from the initial occurrence of an idea to its further exploration and elaboration by a potential entrepreneur. It establishes that the specific situations that induce opportunity insights also affect the roles that individuals’ prior knowledge and learning approaches play for the formation of opportunity intentions. The likelihood of acting on their initial opportunity insights depends not only on how much prior knowledge individuals have of the opportunity domain, but also on whether their learning style matches the situation at hand. The results from an experiment show that domain–specific knowledge enables action when there is a person–situation match and impedes it when such a match is lacking.